1989
DOI: 10.1021/j100341a069
|View full text |Cite
|
Sign up to set email alerts
|

Sodium glyco- and taurodeoxycholate: possible helical models for conjugated bile salt micelles

Abstract: supported on alumina. The appearance of all of the products and the disappearance of one of the reactants (OH-) can be simultaneously followed by FTIR.RhC13 has been shown to react with surface O H groups on alumina at 180 "C. The product of this reaction is believed to be Rh3+ bonded to a surface oxygen on alumina. This species is an intermediate in the room-temperature oxidation of CO listed above.Removal of the surface O H groups by reaction with RhC1, dramatically suppresses the reaction of COz with alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 3 publications
8
77
0
2
Order By: Relevance
“…In the present study, the anionic surfactant taurodeoxycholate (TDC) was used primarily to study its impact on the separation selectivity of some series of PKA peptide substrates, and to identify the structural features of the peptides that determine their distribution to the micelles. TDC forms small (up to ten monomers) reversed micelles of helical structure [28], it contains asymmetric carbon atoms, and has mainly been used in MEKC for chiral separations of derivatized amino acids [29-321 and local anaesthetics [33], but also in nonchiral separations of phthalates [34] and of small peptides [35].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the anionic surfactant taurodeoxycholate (TDC) was used primarily to study its impact on the separation selectivity of some series of PKA peptide substrates, and to identify the structural features of the peptides that determine their distribution to the micelles. TDC forms small (up to ten monomers) reversed micelles of helical structure [28], it contains asymmetric carbon atoms, and has mainly been used in MEKC for chiral separations of derivatized amino acids [29-321 and local anaesthetics [33], but also in nonchiral separations of phthalates [34] and of small peptides [35].…”
Section: Introductionmentioning
confidence: 99%
“…2,6 Although it is well known that bile salts form micelles, the precise structure and dynamics of micellization is still poorly understood. Several models of micelle formation have been proposed in the literature 2,[7][8][9][10][11] and the study of these systems remains an active endeavor. In 1968, Small et al 2 proposed a two-step model of bile salt aggregation, and this model remains one of the more prominent hypotheses in the bile salt literature.…”
mentioning
confidence: 99%
“…9 Alternative models for bile salt aggregation have been suggested, such as by Kawamura et al, 10 who proposed a disk-like micellar model where the hydrophilic surfaces of the bile salt monomer are exposed to the solvent and the hydrophobic surfaces are orientated towards the interior of the micelle. Also, Giglio et al 11 have suggested aggregation that results in a helical micellar structure.…”
mentioning
confidence: 99%
“…Perhaps because humans do not have fur to protect the skin from ultraviolet radiation, we have adapted to have SQ produced in our sebum as a source of protection. It is noteworthy that sebum from most animals do not contain SQ except the otter, beaver, mole and kinkajou which contain up to 94 % SQ in their sebum [32][33][34][35]. All of these species inhabit wet environments suggesting a water repellant function for SQ.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 The structure of the crystalline state suggests a helical arrangement for bile salt micelles. Association of In this model, the head and tail of the bile salt are also labeled to show the anti-parallel arrangement.…”
Section: Postulated Models On the Formation Of Bile Salt Micellesmentioning
confidence: 99%